Nanomechanical probing of soft matter through hydrophobic AFM tips fabricated by two-photon polymerization. (29th February 2016) - Suriano, Raffaella; Zandrini, Tommaso; De Marco, Carmela; Osellame, Roberto; Turri, Stefano; Bragheri, Francesca
Abstract: Atomic force microscopy (AFM) nanoindentation of soft materials is a powerful tool for probing mechanical properties of biomaterials. Though many results have been reported in this field over the last decade, adhesion forces between the tip and the sample hinder the elastic modulus measurement when hydrophilic soft samples are investigated. Here, two-photon polymerization (2PP) technology was used to fabricate hydrophobic perfluoropolyether-based AFM tips. The hydrophobic 2PP tips allowed us to overcome the limitations of commercial and functionalized tips as well as to successfully measure the elastic modulus of medically relevant soft materials in air. Our results obtained in the characterization of poly(dimethyl siloxane) and polyethylene glycol hydrogels showed lower adhesion forces over a larger measurement range when compared to measurements performed with commercial tips. The elastic moduli measured by means of hydrophobic 2PP AFM tips were also found to be comparable to those obtained using conventional techniques for macroscopic samples. We successfully showed that the hydrophobic AFM tips developed by this highly versatile technology enable the study of mechanical properties of soft matter, benefiting from reduced sample–tip interactions, and a custom-made shape and dimension of the tips.